Polyurea-based surface treatment composition for concrete structures and salt damage prevention method using the same

KR103019498B1Active Publication Date: 2026-09-15SIWON GLOBAL CO LTD +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
KR1020260086483
Authority / Receiving Office
KR · KR
Patent Type
Patents
Current Assignee / Owner
Filing Date
2026-05-13
Publication Date
2026-09-15
Estimated Expiration
2046-05-13

Smart Images

  • Figure 112026058025574-PAT00002_ABST
    Figure 112026058025574-PAT00002_ABST
Patent Text Reader

Abstract

The present invention relates to a polyurea-based surface treatment composition for concrete structures and a salt damage prevention method using the same. More specifically, the invention relates to a polyurea-based surface treatment composition in which a first agent and a second agent are mixed in a volume ratio of 1:0.5 to 1.5, wherein the first agent contains 100 parts by weight of an isocyanate prepolymer; 1 to 10 parts by weight of tetrahexyldecyl ascorbate; and 0.1 to 5 parts by weight of phlogopite, and the second agent contains 100 parts by weight of poly(oxypropylene)diamine; 10 to 50 parts by weight of nadic methyl anhydride; 10 to 30 parts by weight of acetoacetanilide; and 10 to 30 parts by weight of diethyltoluenediamine. and contains 1 to 10 parts by weight of one or more polyaspartate salts selected from the group consisting of sodium polyaspartate, potassium polyaspartate, and mixtures thereof, and the isocyanate prepolymer is prepared by reacting 100 parts by weight of norbornane diisocyanate (NBDI); 10 to 30 parts by weight of dimeryl diisocyanate (DDI); 50 to 150 parts by weight of polyoxypropylene glycol; 10 to 30 parts by weight of 3-hydroxyoxetane; and 1 to 10 parts by weight of glycidol, thereby The present invention relates to a polyurea-based surface treatment composition for concrete structures and a salt damage prevention method using the same, which prevents corrosion and cracking by suppressing chloride penetration from the concrete surface into the interior caused by seawater particles carried in large quantities by typhoons or seasonal winds in extreme environments, particularly typhoons or seasonal winds, and prevents damage to the coating film caused by repeated shrinkage and expansion due to thermal expansion or thermal shock, and maintains stable waterproofing performance by enhancing crack-following ability through excellent tensile performance and elongation, as well as effectively reducing yellowing and surface deterioration caused by ultraviolet rays, has excellent adhesion to the surface of the structure, tensile performance and elongation, and has excellent waterproofing, impact resistance, abrasion resistance, chemical resistance, cold resistance, heat resistance, water resistance, durability, and weather resistance, and is applicable regardless of the structure or shape of the surface to be coated, and is easy to apply according to site conditions such as spraying, roller, or brushing.
Need to check novelty before this filing date? Find Prior Art

Description

Technology Field

[0001] The present invention relates to a polyurea-based surface treatment composition for concrete structures and a salt damage prevention method using the same, which prevents corrosion and cracking by suppressing chloride penetration from the concrete surface into the interior caused by seawater particles carried in large quantities by typhoons or seasonal winds in extreme environments, particularly typhoons or seasonal winds, prevents damage to the coating film caused by repeated shrinkage and expansion due to thermal expansion or thermal shock, maintains stable waterproofing performance by enhancing crack-following ability through excellent tensile performance and elongation, and effectively reduces yellowing and surface deterioration caused by ultraviolet rays, has excellent adhesion to the surface of the structure, tensile performance and elongation, and has excellent waterproofing, impact resistance, abrasion resistance, chemical resistance, cold resistance, heat resistance, water resistance, durability, and weather resistance, is applicable regardless of the structure or shape of the surface to be coated, and is easy to apply according to site conditions such as spraying, rollers, and brushes. Background Technology

[0003] Generally, concrete structures possess excellent durability and compressive strength; however, over time, aging is accelerated by physical, chemical, and environmental factors. More specific examples of this aging include various deterioration phenomena such as increased porosity, cracking, aggregate exposure, surface spalling, reduced strength, exposed and corroded rebar, chloride ion penetration, salt damage, carbonation, and leakage. In particular, due to the inherent coefficient of thermal expansion of concrete, it repeatedly shrinks and expands around its center in response to temperature changes, leading to cracks that allow water or rain to penetrate the building structure. Consequently, the performance and durability of concrete structures deteriorate, potentially causing serious problems for the actual structures.

[0004] Accordingly, the aforementioned problems were resolved by applying waterproofing construction using various waterproofing materials to prevent corrosion or damage caused by moisture on the rooftops, roofs, floors, interior and exterior walls, parking lots, swimming pools, water purification plants, drainage plants, water supply walls, etc., of concrete structures.

[0005] Conventional surface waterproofing methods for concrete structures, such as applying asphalt or coal tar pitch to form a waterproofing layer, have the advantages of being easy to apply and relatively inexpensive. However, they suffer from poor durability and easy cracking, which leads to water penetration, loss of waterproofing performance, or rapid deterioration of durability. Additionally, conventional surface waterproofing methods for concrete structures, such as applying urethane-based or epoxy-based waterproofing materials to form a waterproofing layer, have the problem that incomplete curing is prone to occur depending on working conditions and requires a long curing time, particularly during the winter, which necessitates a drying time of more than 24 hours. Furthermore, they fail to adequately track microcracks, thermal shrinkage, vibration, and repeated deformation of the concrete, leading to problems such as the possibility of cracking or delamination during long-term use.

[0006] In order to improve upon the problems of the aforementioned surface waterproofing construction methods for concrete structures, a construction method involving the application of polyurea-based materials to form a waterproof layer is widely used these days.

[0007] These polyurea-based materials have excellent tensile performance and elongation, and their fast curing speed not only shortens construction time but also, compared to urethane or epoxy resins, they are hydrophobic, allowing for direct spraying even on moist or low-temperature surfaces, and offering the advantage of freely adjusting the film thickness to the desired level.

[0008] On the other hand, problems such as pinholes or uneven surfaces occurred depending on the watertightness of the concrete substrate. Furthermore, despite the excellent adhesion resulting from the significant shrinkage caused by ultra-fast curing—which begins immediately upon application—problems of lifting or delamination from the concrete substrate still remain. Additionally, since polyurea-based materials possess elastomer properties similar to synthetic rubber, there is still a problem where their physical properties and durability can rapidly deteriorate due to ultraviolet rays and atmospheric pollutants after application to concrete structures.

[0009] Furthermore, structures in the atmosphere or underwater, such as harbor structures made of concrete or steel, underground structures, exposed structures, bridge structures frequently subjected to repeated wetting and drying, and structures chemically eroded by calcium chloride, SOx, NOx, etc., suffer reduced durability due to polluted air as well as weather conditions like rain, wind, snow, and sunlight, and also due to salt or chlorides present in brine. In particular, if the aforementioned salt or chlorides penetrate and spread into the structure, concrete and rebar corrode prematurely. As chlorides attract a large amount of moisture, the structure undergoes volumetric expansion, leading to cracking and spalling. If proper maintenance is not performed, this can even result in collapse. This problem occurs frequently in structures directly exposed to de-icing agents and ice-melting agents used during the winter, as well as in underwater structures and cases where chlorides adhere to concrete surfaces. Prior art literature

[0011] Republic of Korea Registered Patent No. 10-2161937 Republic of Korea Registered Patent No. 10-2312381 Republic of Korea Registered Patent No. 10-2191257 The problem to be solved

[0012] The present invention has been devised to solve the aforementioned problems. One embodiment of the present invention aims to provide a polyurea-based surface treatment composition for concrete structures and a salt damage prevention method using the same, which can prevent corrosion, cracking, and peeling by inhibiting chloride adhesion to the concrete surface and chloride penetration into the interior, and not only form a physically and chemically stable coating film by enhancing crack-following properties but also improve outdoor weather resistance by reducing yellowing and surface deterioration caused by ultraviolet rays.

[0013] The various problems that the present invention aims to solve are not limited to those mentioned above, and other unmentioned problems will be clearly understood by those skilled in the art from the description below. means of solving the problem

[0015] One embodiment of the present invention is a polyurea-based surface treatment composition in which a first agent and a second agent are mixed in a volume ratio of 1:0.5 to 1.5, wherein the first agent contains 100 parts by weight of an isocyanate prepolymer; 1 to 10 parts by weight of tetrahexyldecyl ascorbate; and 0.1 to 5 parts by weight of phlogopite,

[0016] The second agent comprises 100 parts by weight of poly(oxypropylene)diamine; 10 to 50 parts by weight of nadic methyl anhydride; 10 to 30 parts by weight of acetoacetanilide, 10 to 30 parts by weight of diethyltoluenediamine; and 1 to 10 parts by weight of one or more polyaspartate salts selected from the group consisting of sodium polyaspartate, potassium polyaspartate, and mixtures thereof, and

[0017] The present invention provides a polyurea-based surface treatment composition for concrete structures, wherein the isocyanate prepolymer is prepared by reacting 100 parts by weight of norbornane diisocyanate (NBDI); 10 to 30 parts by weight of dimeryl diisocyanate (DDI); 50 to 150 parts by weight of polyoxypropylene glycol; 10 to 30 parts by weight of 3-hydroxyoxetane; and 1 to 10 parts by weight of glycidol.

[0018] The above-mentioned flogophite is

[0019] It is a plogopite coated with an adhesive polymer, and

[0020] The above-mentioned adhesive polymer-coated phlogopite comprises the steps of: preparing a phlogopite dispersion by mixing 100 parts by weight of distilled water, 200 to 400 parts by weight of methanol, 1 to 10 parts by weight of an aqueous hydrochloric acid solution having a concentration of 30 to 40 wt%, 0.01 to 1 part by weight of a sulfoxymine compound, and 10 to 30 parts by weight of phlogopite; and preparing a monomer mixture by mixing N-vinylpyrrolidone, butyl acrylate, and azobisisobutyronitrile (AIBN) polymerization initiator in a weight ratio of 1:0.8 to 1.2:0.01 to 0.3. and a step of producing phlogopite coated with an adhesive polymer by adding 1 to 20 parts by weight of the monomer mixture drop by drop to 100 parts by weight of the solid content of the phlogopite dispersion at 50 to 80 ℃, and then reacting for 4 to 8 hours; and

[0021] The above sulfoxymine compound may be one or more selected from the group consisting of thionine sulfoxymine, methionine sulfoxymine, 2-ethylmethionine sulfoxymine, and mixtures thereof.

[0022] The step of manufacturing the plogopite coated with the above adhesive polymer is

[0023] In a dispersion mixture comprising 100 parts by weight of the solid content of the phlogopite dispersion, 1 to 10 parts by weight of hydrogenated lecithin, 1 to 10 parts by weight of alumina fiber, and 1 to 5 parts by weight of hydroxypropyl cyclodextrin (HPCD), 1 to 20 parts by weight of the monomer mixture may be added drop by drop to a dispersion mixture mixed at 50 to 80 ℃, and then reacted for 4 to 8 hours.

[0024] The above isocyanate prepolymer is

[0025] The above-mentioned norbornane diisocyanate further contains 1 to 10 parts by weight of a cardol-based compound per 100 parts by weight, and

[0026] The above cardol compound may be one or more selected from the group consisting of cardol diene (CAS No. 79473-25-9), cardol triene (CAS No. 79473-24-8), and mixtures thereof.

[0027] The above first product

[0028] The above isocyanate prepolymer further contains 1 to 10 parts by weight of a pelargonate-based compound per 100 parts by weight, and

[0029] The above pelargonate-based compound may be one or more selected from the group consisting of neopentyl glycol dipelagonate, glycerol tripelagonate, pentaerythritol tetrapelagonate, and mixtures thereof.

[0030] In addition, another embodiment of the present invention is a salt damage prevention method using the polyurea-based surface treatment composition for concrete structures, wherein

[0031] A salt damage prevention method is provided comprising: a surface preparation step of removing impurities, laitance, and deteriorated areas from the surface of a concrete structure and cleaning to prepare the surface; a primer layer formation step of applying one or more primers selected from the group consisting of silane-based primers, siloxane-based primers, silane-siloxane composite primers, silicate-based primers, epoxy-silane composite primers, and mixtures thereof; a polyurea-based intermediate layer formation step of applying a polyurea-based surface treatment composition for the concrete structure; and a weather-resistant top layer formation step of applying one or more top coating agents selected from the group consisting of aliphatic polyurea-based, polyaspartic-based, aliphatic urethane-based, and mixtures thereof. Effects of the invention

[0033] According to a polyurea-based surface treatment composition for concrete structures and a salt damage prevention method using the same according to one embodiment of the present invention, there is an effect of preventing corrosion and cracking by suppressing the penetration of chlorides from the concrete surface into the interior by seawater particles carried in large quantities by extreme environments, particularly typhoons or seasonal winds.

[0034] In addition, it prevents damage to the coating film caused by repeated shrinkage and expansion due to thermal expansion or thermal shock, and enhances crack-following ability through excellent tensile performance and elongation, thereby maintaining stable waterproofing performance and effectively reducing yellowing and surface deterioration caused by ultraviolet rays, which has the effect of improving long-term outdoor exposure performance.

[0035] In addition, it has the effect of forming a high-quality waterproof coating with excellent adhesion to the surface of the structure, tensile performance, and elongation, as well as excellent water resistance, impact resistance, abrasion resistance, chemical resistance, cold resistance, heat resistance, water resistance, durability, and weather resistance.

[0036] In addition, it is applicable regardless of the structure or shape of the surface to be painted, and can be applied according to site conditions using methods such as spraying, rollers, and brushes, offering the advantage of easy construction.

[0037] Therefore, it can be advantageously used when applied to coastal structures, harbor structures, bridges, piers, abutments, guardrails, retaining walls, water treatment structures, precast concrete structures, and concrete structures exposed to de-icing salts. Brief explanation of the drawing

[0039] Figure 1 shows a schematic construction sequence diagram of a salt damage prevention method according to one embodiment of the present invention. FIGS. 2 to 5 show the results of a performance test according to Example 1 of the present invention. Specific details for implementing the invention

[0040] Hereinafter, embodiments of the present invention will be described in detail. However, these are presented as examples and are not intended to limit the present invention, and the present invention is defined only by the scope of the claims set forth below.

[0041] One embodiment of the present invention is a polyurea-based surface treatment composition in which a first agent and a second agent are mixed in a volume ratio of 1:0.5 to 1.5, wherein the first agent contains 100 parts by weight of an isocyanate prepolymer; 1 to 10 parts by weight of tetrahexyldecyl ascorbate; and 0.1 to 5 parts by weight of phlogopite,

[0042] The second agent comprises 100 parts by weight of poly(oxypropylene)diamine; 10 to 50 parts by weight of nadic methyl anhydride; 10 to 30 parts by weight of acetoacetanilide, 10 to 30 parts by weight of diethyltoluenediamine; and 1 to 10 parts by weight of one or more polyaspartate salts selected from the group consisting of sodium polyaspartate, potassium polyaspartate, and mixtures thereof, and

[0043] The present invention relates to a polyurea-based surface treatment composition for concrete structures, wherein the isocyanate prepolymer is prepared by reacting 100 parts by weight of norbornane diisocyanate (NBDI); 10 to 30 parts by weight of dimeryl diisocyanate (DDI); 50 to 150 parts by weight of polyoxypropylene glycol; 10 to 30 parts by weight of 3-hydroxyoxetane; and 1 to 10 parts by weight of glycidol.

[0044] According to a polyurea-based surface treatment composition for concrete structures and a salt damage prevention method using the same according to one embodiment of the present invention, it is possible to prevent corrosion and cracking by suppressing the penetration of chlorides from the concrete surface into the interior caused by seawater particles carried in large quantities by extreme environments, particularly typhoons or seasonal winds. In addition, it is possible to prevent damage to the coating film due to repeated shrinkage and expansion caused by thermal expansion or thermal shock, and by enhancing crack-following properties through excellent tensile performance and elongation, it is possible to maintain stable waterproofing performance and effectively reduce yellowing and surface deterioration caused by ultraviolet rays, thereby improving long-term outdoor exposure performance. Furthermore, it is possible to form a high-quality waterproof coating film with excellent adhesion to the surface of the structure, tensile performance and elongation, and excellent waterproofing, impact resistance, abrasion resistance, chemical resistance, cold resistance, heat resistance, water resistance, durability, and weather resistance. In addition, it is applicable regardless of the structure or shape of the surface to be painted, and can be applied according to site conditions using methods such as spraying, rollers, and brushes, offering the advantage of easy construction.

[0045] Therefore, it can be advantageously used when applied to coastal structures, harbor structures, bridges, piers, abutments, guardrails, retaining walls, water treatment structures, precast concrete structures, and concrete structures exposed to de-icing salts.

[0046] A polyurea-based surface treatment composition for concrete structures according to one embodiment of the present invention can achieve the above-mentioned effect by reacting a first agent having an isocyanate group and a second agent having an amine group. By mixing the first agent and the second agent in a volume ratio of 0.5 to 1.5 to achieve a sufficient reaction without any unreacted residual components, the above-mentioned effect of the present invention can be maximized.

[0047] More specifically, the first agent may be used that contains 100 parts by weight of isocyanate prepolymer; 1 to 10 parts by weight of tetrahexyldecyl ascorbate; and 0.1 to 5 parts by weight of phlogopite.

[0048] The above isocyanate prepolymer is obtained by polymerizing an isocyanate containing an isocyanate group with a polyol, and refers to the prepolymerized isocyanate.

[0049] Specifically, a composition containing 100 parts by weight of norbornane diisocyanate (NBDI); 10 to 30 parts by weight of dimeryl diisocyanate (DDI); 50 to 150 parts by weight of polyoxypropylene glycol; 10 to 30 parts by weight of 3-hydroxyoxetane; and 1 to 10 parts by weight of glycidol may be used.

[0050] The above norbornane diisocyanate (NBDI) has excellent tensile strength, tear strength, and wear resistance, and plays a role in preventing delamination, peeling, and cracking by suppressing chloride penetration under harsh external conditions, particularly by seawater particles. In addition, it exhibits stability against UV rays, preventing yellowing and providing excellent processability.

[0051] The above-mentioned dimeryl diisocyanate improves heat resistance, wear resistance, resistance to permanent compression deformation, and resilience, and enhances salt damage resistance by improving processability and stability.

[0052] Such dimeryl diisocyanate can be used in an amount of 10 to 30 parts by weight per 100 parts by weight of norbornane diisocyanate. If the content of the dimeryl diisocyanate is below the above range, there is a problem that the above-mentioned improvement effect may be insufficient, and if the content of the dimeryl diisocyanate exceeds the above range, there is a problem that the responsiveness to the behavior of the substrate surface or the wear resistance may be reduced.

[0053] The above polyoxypropylene glycol provides responsiveness to the behavior of the substrate surface through excellent tensile strength, tear strength, and elongation, enabling the formation of a coating film with excellent smoothness and flexibility without pinhole formation, and serves to provide excellent waterproofing and corrosion resistance performance. In addition, since both heat resistance and cold resistance are improved, construction is easy not only in summer but also in winter, and it provides excellent workability by offering excellent adhesion performance on wet surfaces as well as dry surfaces.

[0054] The molecular weight (number average molecular weight) of the above polyoxypropylene glycol may be 1,000 to 6,000. If the molecular weight of the above polyoxypropylene glycol is excessively high, the hardness and impact resistance of the coating film may be reduced, and if the molecular weight is excessively low, the waterproofing performance may be reduced. Preferably, the molecular weight (number average molecular weight) of the above polyoxypropylene glycol may be 1,000 to 3,000.

[0055] This polyoxypropylene glycol can be used in an amount of 50 to 150 parts by weight per 100 parts by weight of norbornane diisocyanate. If the content of the polyoxypropylene glycol is below the above range, there is a problem that the above-mentioned improvement effect may be insufficient, and if the content of the polyoxypropylene glycol exceeds the above range, there is a problem that the viscosity increases, curing is delayed, making spray coating impossible, and adhesion may be reduced.

[0056] The above 3-hydroxyoxetane rapidly penetrates into the pores or cracks of the concrete structure and forms a network to densely reinforce the internal structure, thereby preventing damage to the coating film caused by repeated shrinkage and expansion due to thermal expansion or thermal shock, and improves physical properties such as tensile strength, elongation, peel strength, and impact strength, thereby playing a role in improving durability such as salt resistance and water resistance in the long term.

[0057] 10 to 30 parts by weight of such 3-hydroxyoxetane can be used per 100 parts by weight of norbornane diisocyanate. If the content of the 3-hydroxyoxetane is less than the above range, there is a problem that the above improvement effect may be insufficient, and if the content of the 3-hydroxyoxetane exceeds the above range, there is a problem that mechanical properties and processability may be reduced.

[0058] The above glycidol plays a role in maximizing adhesion and crosslinking properties to improve mechanical strength such as tensile strength and wear resistance, as well as heat resistance and elasticity, and also improves chemical resistance and salt resistance.

[0059] 1 to 10 parts by weight of such glycidol may be used per 100 parts by weight of norbornane diisocyanate. If the content of the glycidol is below the above range, there is a problem that the above-mentioned improvement effect may be insufficient, and if the content of the glycidol exceeds the above range, there is a problem that durability and processability may be reduced.

[0060] In addition, the isocyanate prepolymer according to one embodiment of the present invention may further contain 1 to 10 parts by weight of a cardol compound per 100 parts by weight of norbornane diisocyanate.

[0061] The above-mentioned cardol-based compound effectively extends the chain and imparts excellent crosslinking performance to strengthen the network structure, and plays a role in improving mechanical strength such as tensile strength and wear resistance, as well as heat resistance and elasticity.

[0062] The above cardol compound may be one or more selected from the group consisting of cardoldine (CAS No. 79473-25-9), cardoldine (CAS No. 79473-24-8), and mixtures thereof.

[0063] Hereinafter, the content of other components constituting the first agent is based on 100 parts by weight of the isocyanate prepolymer.

[0064] The above tetrahexyldecyl ascorbate (CAS No. 183476-82-6) inhibits yellowing and decomposition without interfering with the NCO reaction, and has excellent durability against light and heat, making it easy to achieve transparency, as well as improving storage stability, adhesion, and leveling performance of the coating surface.

[0065] Such tetrahexyldecyl ascorbate can be used in an amount of 1 to 10 parts by weight per 100 parts by weight of isocyanate prepolymer. If the content of the tetrahexyldecyl ascorbate is less than the above range, there is a problem that the above improvement effect may be insufficient, and if the content of the tetrahexyldecyl ascorbate exceeds the above range, there is a problem that phase separation and curing delay may occur.

[0066] The above-mentioned phlogopite is a magnesium-rich biotite-based mineral that possesses excellent impact resistance and wear resistance, and plays a role in improving salt resistance by dispersing stress and suppressing cracking. In addition, it plays a role in preventing pinholes, lifting, and delamination caused by the ultra-fast curing of polyurea by suppressing shrinkage forces that occur during the curing process.

[0067] In addition, to further enhance the above-mentioned improvement effect, as well as to improve adhesion and maintain uniform physical properties of the coating film through uniform dispersion, plogopite coated with an adhesive polymer can be used.

[0068] Specifically, the phlogopite coated with the adhesive polymer comprises the steps of: preparing a phlogopite dispersion by mixing 100 parts by weight of distilled water, 200 to 400 parts by weight of methanol, 1 to 10 parts by weight of an aqueous hydrochloric acid solution having a concentration of 30 to 40 wt%, 0.01 to 1 part by weight of a sulfoxymine compound, and 10 to 30 parts by weight of phlogopite; and preparing a monomer mixture by mixing N-vinylpyrrolidone, butyl acrylate, and azobisisobutyronitrile (AIBN) polymerization initiator in a weight ratio of 1:0.8 to 1.2:0.01 to 0.3. It can be manufactured by a method comprising the step of: adding 1 to 20 parts by weight of the monomer mixture drop by drop to 100 parts by weight of the solid content of the phlogopite dispersion at 50 to 80 ℃, and then reacting for 4 to 8 hours to produce phlogopite coated with an adhesive polymer. At this time, the solid content of the phlogopite dispersion refers to the content of phlogopite excluding the solvent from the entire dispersion.

[0069] The above sulfoxymine compound plays a role in improving not only the efficiency of the polymerization reaction but also the coating uniformity of the adhesive polymer, and may be, for example, one or more selected from the group consisting of thionine sulfoxymine, methionine sulfoxymine, 2-ethylmethionine sulfoxymine, and mixtures thereof.

[0070] In addition, the step of manufacturing phlogopite coated with an adhesive polymer may further include alumina fibers, hydrogenated lecithin (CAS No. 92128-87-5), and hydroxypropyl cyclodextrin (HPCD, CAS No. 128446-35-5) to maintain stable adhesion against external temperature changes and improve long-term salt resistance and water resistance.

[0071] Specifically, the step of preparing the phlogopite coated with the adhesive polymer can be carried out by adding 1 to 20 parts by weight of the monomer mixture drop by drop to a dispersion mixture comprising 100 parts by weight (based on solid content) of the phlogopite dispersion, 1 to 10 parts by weight of hydrogenated lecithin, 1 to 10 parts by weight of alumina fiber, and 1 to 5 parts by weight of hydroxypropyl cyclodextrin (HPCD) at 50 to 80 ℃, and then reacting for 4 to 8 hours.

[0072] At this time, the average diameter of the alumina fiber may be 0.1 to 5 μm and the average length may be 0.01 to 1 mm, more preferably the average diameter may be 0.5 to 3 μm and the average length may be 0.03 to 0.5 mm, and even more preferably the average diameter may be 1 to 2 μm and the average length may be 0.05 to 0.2 mm. Using staple fibers is advantageous as it facilitates mixing with other components and can maximize tensile strength and elongation.

[0073] The above hydrogenated lecithin and hydroxypropyl cyclodextrin improve the dispersibility and compatibility of alumina fibers, thereby improving the adhesion between the adhesive polymer and the alumina fibers and facilitating the formation of a uniform coating film.

[0074] Such phlogopite can be used in an amount of 0.1 to 5 parts by weight per 100 parts by weight of isocyanate prepolymer. If the content of the phlogopite is less than the above range, there is a problem that the above improvement effect may be insufficient, and if the content of the phlogopite exceeds the above range, there is a problem that the adhesive strength is reduced, interlayer delamination increases, and workability and economic efficiency may be reduced.

[0075] In addition, the first agent according to the present invention may further contain 1 to 10 parts by weight of a pelargonate-based compound per 100 parts by weight of the isocyanate prepolymer.

[0076] The above-mentioned pelargonate-based compound plays a role in improving adhesion to the surface of concrete structures, rapid hardening, chemical resistance, abrasion resistance, cold resistance, durability, and weather resistance.

[0077] The pelargonate compounds may be one or more selected from the group consisting of neopentyl glycol dipelagonate, glycerol tripelagonate, pentaerythritol tetrapelagonate, and mixtures thereof.

[0078] In addition, the second agent of the present invention may be used to contain 100 parts by weight of poly(oxypropylene)diamine; 10 to 50 parts by weight of nadic methyl anhydride; 10 to 30 parts by weight of acetoacetanilide; 10 to 30 parts by weight of diethyltoluenediamine; and 1 to 10 parts by weight of one or more polyaspartate salts selected from the group consisting of sodium polyaspartate, potassium polyaspartate, and mixtures thereof.

[0079] The above poly(oxypropylene)diamine causes rapid curing through a rapid reaction with the above first agent, thereby improving adhesion strength, compressive strength, tensile strength, tear strength, and elongation to enhance responsiveness to substrate behavior, while simultaneously improving excellent waterproofing and corrosion resistance, water resistance, salt resistance, chemical resistance (acid resistance, alkali resistance), abrasion resistance, heat resistance, UV resistance, and durability.

[0080] Hereinafter, the content of other components constituting the second agent is based on 100 parts by weight of the poly(oxypropylene)diamine.

[0081] The above-mentioned nadic methyl anhydride serves to terminate the reaction, control the rate, enhance stability in high-temperature environments, improve the wear resistance, heat resistance, and thermal conductivity of the coating film, and improve sprayability.

[0082] Such nadic methyl anhydride can be used in an amount of 10 to 50 parts by weight per 100 parts by weight of poly(oxypropylene)diamine. If the content of the nadic methyl anhydride is below the above range, there is a problem that the above improvement effect may be insufficient, and if the content of the nadic methyl anhydride exceeds the above range, there is a problem that phase separation occurs, which may reduce mechanical strength and transparency.

[0083] The above acetoacetanilide acts as a chain extension aid that imparts flexibility and processability, and not only provides stability against light but also plays a role in improving adhesion and workability during spray coating.

[0084] Such acetoacetanilide can be used in an amount of 10 to 30 parts by weight per 100 parts by weight of poly(oxypropylene)diamine. If the content of the acetoacetanilide is below the above range, there is a problem that the above-mentioned improvement effect may be insufficient, and if the content of the acetoacetanilide exceeds the above range, there is a problem that the adhesive strength and durability may be reduced.

[0085] The above-mentioned diethyltoluenediamine enhances the curing speed by increasing the crosslinking reaction and plays a role in improving responsiveness to substrate behavior through excellent adhesion strength and compressive strength, as well as excellent tensile strength, tear strength, and elongation.

[0086] The above diethyltoluenediamine may be used in an amount of 10 to 30 parts by weight per 100 parts by weight of the above poly(oxypropylene)diamine. If the content of the above diethyltoluenediamine is less than the above range, there is a problem that the above improvement effect may be insufficient, and if the content of the above diethyltoluenediamine exceeds the above range, there is a problem that the smoothness of the coating film may be reduced.

[0087] The above polyaspartate salt plays a role in improving not only excellent adhesion strength but also excellent waterproofing, salt resistance, water resistance, and durability.

[0088] The above polyaspartate salt may be one or more selected from the group consisting of sodium polyaspartate (CAS No. 94525-01-6), potassium polyaspartate (CAS No. 64723-18-8), and mixtures thereof.

[0089] The above polyaspartate salt may be used in an amount of 1 to 10 parts by weight per 100 parts by weight of the above poly(oxypropylene)diamine. If the content of the above polyaspartate salt is less than the above range, there is a problem that the above improvement effect may be insufficient, and if the content of the above polyaspartate salt exceeds the above range, there is a problem that price competitiveness may be reduced.

[0090] In addition, another embodiment of the present invention relates to a salt damage prevention method using the polyurea-based surface treatment composition for concrete structures, comprising: a surface preparation step of removing impurities, laitance, and deteriorated areas from the surface of a concrete structure and cleaning to prepare the base surface; a primer layer formation step of applying one or more primers selected from the group consisting of silane-based primers, siloxane-based primers, silane-siloxane composite primers, silicate-based primers, epoxy-silane composite primers, and mixtures thereof; a polyurea-based intermediate layer formation step of applying the polyurea-based surface treatment composition for concrete structures; and a weather-resistant top layer formation step of applying one or more top coating agents selected from the group consisting of aliphatic polyurea-based, polyaspartic-based, aliphatic urethane-based, and mixtures thereof. By using a construction method utilizing such a multilayer coating system, performance improvement and economic efficiency can be secured simultaneously. A construction sequence diagram of a construction method using a polyurea-based surface treatment composition for concrete structures according to one embodiment of the present invention is shown in Fig. 1 below.

[0091] The above surface preparation step can be performed by removing impurities, laitance, and deteriorated areas on the surface of the concrete structure using conventional cutting equipment such as planers, grinders, shot blasters, and polishers, and by cleaning using conventional cleaning equipment such as high-pressure water jets and vacuum cleaners.

[0092] The step of forming the primer layer is performed to penetrate into the pores of the concrete surface to stabilize residual pores and fine dust, and to facilitate the adhesion of the polyurea-based surface treatment composition for concrete structures to the concrete structure, thereby reducing the possibility of peeling.

[0093] The step of applying the above-described polyurea-based surface treatment composition for concrete structures can be performed by mixing the above-described first agent and second agent in a dedicated coating device and then spraying. More specifically, the above-described first agent and second agent can be introduced into a dedicated spray gun, mixed by impact under high temperature and high pressure, and then sprayed. More preferably, the application can be performed by heating and maintaining the temperature at 60 to 80 ℃ and spraying at a spray pressure of 2,000 to 3,500 psi. However, the present invention is not limited thereto, and it is obvious that the first agent and second agent of the above-described polyurea-based surface treatment composition for concrete structures may be screw-mixed by a static mixer under low temperature and low pressure conditions.

[0094] The application of the above polyurea-based surface treatment composition for concrete structures may be performed 1 to 3 times, and the thickness of the formed film may be 0.5 to 3.5 mm.

[0095] The step of forming the above weather-resistant topcoat is performed to ensure weather resistance by suppressing deterioration caused by ultraviolet rays and climate change, to protect the concrete surface from the external environment (rain, pollutants, temperature changes, etc.), and to maintain appearance and durability in the long term by reducing surface wear.

[0096] The top coating agent used to form the weather-resistant top layer may further include one or more additives selected from the group consisting of UV absorbers, light stabilizers (HALS), pigments, water-repellent agents, anti-fouling additives, and mixtures thereof.

[0097] According to a polyurea-based surface treatment composition for concrete structures and a salt damage prevention method using the same according to one embodiment of the present invention, it is possible to prevent corrosion and cracking by suppressing the penetration of chlorides from the concrete surface into the interior caused by seawater particles carried in large quantities by extreme environments, particularly typhoons or seasonal winds. In addition, it is possible to prevent damage to the coating film due to repeated shrinkage and expansion caused by thermal expansion or thermal shock, and by enhancing crack-following properties through excellent tensile performance and elongation, it is possible to maintain stable waterproofing performance and effectively reduce yellowing and surface deterioration caused by ultraviolet rays, thereby improving long-term outdoor exposure performance. Furthermore, it is possible to form a high-quality waterproof coating film with excellent adhesion to the surface of the structure, tensile performance and elongation, and excellent waterproofing, impact resistance, abrasion resistance, chemical resistance, cold resistance, heat resistance, water resistance, durability, and weather resistance. In addition, it is applicable regardless of the structure or shape of the surface to be painted, and can be applied according to site conditions using methods such as spraying, rollers, and brushes, offering the advantage of easy construction.

[0098] Therefore, it can be advantageously used when applied to coastal structures, harbor structures, bridges, piers, abutments, guardrails, retaining walls, water treatment structures, precast concrete structures, and concrete structures exposed to de-icing salts.

[0099] Although preferred embodiments of the present invention have been described in detail above, the present invention is not limited to the above embodiments, and various modifications are possible by those skilled in the art within the scope of the technical concept of the present invention.

[0101] <Preparation Example 1> Phlogopite coated with adhesive polymer

[0102] A phlogopite dispersion was prepared by mixing 100 parts by weight of distilled water, 350 parts by weight of methanol, 7 parts by weight of an aqueous hydrochloric acid solution with a concentration of 30 wt%, 0.05 parts by weight of thionine sulfoxymine, and 25 parts by weight of phlogopite at room temperature. At this time, an ice bath was used to maintain the temperature so that it did not rise. Separately, a monomer mixture was prepared by mixing N-vinylpyrrolidone, butyl acrylate, and azobisisobutyronitrile (AIBN) polymerization initiator in a weight ratio of 1:1:0.025. Subsequently, at 60°C, 10 parts by weight of the prepared monomer mixture were added drop by drop to 100 parts by weight of the solid content of the prepared phlogopite dispersion, and the mixture was reacted for 6 hours to produce phlogopite coated with an adhesive polymer.

[0104] <Preparation Example 2> Phlogopite coated with adhesive polymer

[0105] The above procedure was carried out in the same manner as Preparation Example 1, but at 60°C, 10 parts by weight of the monomer mixture prepared above were added drop by drop to a dispersion mixture comprising 100 parts by weight of the solid content of the prepared phlogopite dispersion, 5 parts by weight of hydrogenated lecithin, 5 parts by weight of alumina fiber, and 3 parts by weight of hydroxypropyl cyclodextrin (HPCD), and then reacted for 6 hours to produce phlogopite coated with an adhesive polymer.

[0107] <Preparation Example 3> Isocyanate prepolymer

[0108] 100 parts by weight of norbornan diisocyanate (NBDI), 5 parts by weight of dimeryl diisocyanate (DDI), 90 parts by weight of polyoxypropylene glycol (Mw: 1500 g / mol), 25 parts by weight of 3-hydroxyoxetane, and 3 parts by weight of glycidol were mixed and reacted at 80°C for 6 hours to prepare an isocyanate prepolymer.

[0110] <Preparation Example 4> Isocyanate prepolymer

[0111] 100 parts by weight of norbornane diisocyanate (NBDI), 5 parts by weight of dimeryl diisocyanate (DDI), 90 parts by weight of polyoxypropylene glycol (Mw: 1500 g / mol), 20 parts by weight of 3-hydroxyoxetane, 5 parts by weight of glycidol, and 5 parts by weight of cardoldien were mixed and reacted at 80°C for 6 hours to prepare an isocyanate prepolymer.

[0113] <Comparative Preparation Example 1>

[0114] 100 parts by weight of methylene diphenyl diisocyanate (MDI), 5 parts by weight of toluene diisocyanate (TDI), 90 parts by weight of polyoxypropylene glycol (Mw: 1500 g / mol), and 30 parts by weight of polytetramethylene ether glycol were mixed and reacted at 80°C for 6 hours to prepare an isocyanate prepolymer.

[0116] <Examples and Comparative Examples>

[0117] A polyurea-based surface treatment composition for concrete structures and a comparative composition were prepared by mixing under the component and content conditions as shown in Table 1 below.

[0118] Classification (Volume Ratio) Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 First 1 1 1 1 1 weight part isocyanate prepolymer 100 [Manufacturing Example 3] 100 [Manufacturing Example 3] 100 [Preparation Example 4] 100 [Comparative Manufacturing Example 1] 100 [Manufacturing Example 3] Tetrahexyldecyl ascorbate 6 6 6 - - Flogopite 3 3 [Manufacturing Example 1] 3 [Manufacturing Example 2] - - alumina fiber - - - - 3 Neopentyl glycol dipelagonate - 2 1 - - Pentaerythritol tetrapelagonate - - 1 - - 2nd 1 1 1 1 1 weight part Poly(oxypropylene)diamine 100 100 100 100 100 Nadic methyl anhydride [CAS No. 25134-21-8] 28 28 28 - - Acetanilide 14 14 14 - - diethyltoluenediamine 12 12 12 12 12 Sodium polyaspartate - 2 2 - - potassium polyaspartate - 2 2 - -

[0120] In the following, experimental results comparing the characteristics of the examples according to the present invention and the comparative compositions prepared according to Comparative Examples 1 and 2 are presented so that the characteristics of the polyurea-based surface treatment compositions for concrete structures prepared according to Examples 1 to 3 above can be more easily identified.

[0121] <Test Example>

[0122] In a separately prepared test specimen, the first agent and the second agent prepared in the above examples and comparative examples, respectively, were introduced and mixed in a dedicated spray gun, and then spray-coated at a temperature of 65°C and a spray pressure of 2,500 psi to prepare the test specimen.

[0123] For the above-mentioned test specimens, the coating properties were evaluated, and the results are shown in Table 2 and Figure 2 below.

[0124] item Test method Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Touch-dry time (sec) KS F 4922 34 30 28 54 46 Tensile strength (N / mm²) 2 ) 23 22 25 9 13 Elongation at break (%) 511 525 536 207 268 Tear performance (N / mm) 82 85 86 33 43 Tensile strength ratio (%) -20℃ 208 212 215 103 145 60℃ 81 80 83 40 61 Growth rate (%) -20℃ 130 135 138 74 96 20℃ 292 307 315 110 145 60℃ 373 394 207 111 156 Heat-stretchable properties (%) -0.18 -0.14 -0.10 3.22 2.19 Tensile strength ratio (%) After heat treatment 80 83 86 52 64 After alkali treatment 112 114 117 71 95 After acid treatment 107 103 105 69 88 After sodium chloride treatment 96 103 105 71 90 After accelerated exposure treatment 93 104 101 64 86 Elongation at break (%) After heat treatment 445 456 472 187 223 After alkali treatment 463 467 472 195 257 After acid treatment 510 515 523 147 284 After sodium chloride treatment 434 436 443 155 270 After accelerated exposure treatment 445 456 463 112 264 Deterioration characteristics upon extension After heat treatment No issues No issues No issues Cracks appear Cracks appear After accelerated exposure treatment No issues No issues No issues Cracks appear Cracks appear ozone treatment No issues No issues No issues Cracks appear Cracks appear Adhesion performance Unprocessed 2.6 2.8 3.0 1.1 1.5 After immersion in water 2.4 2.4 2.6 0.9 1.3 After alkali treatment 2.2 2.1 2.4 0.8 1.2 After acid treatment 1.9 2.2 2.3 0.9 1.3 After sodium chloride treatment 2.2 2.3 2.3 1.1 1.4 After accelerated exposure treatment 2.5 2.5 2.6 1.3 1.6 Fatigue resistance No issues No issues No issues Excitement Excitement Hardness (Shore D) ASTM 2240 44 45 49 31 35 Thermal conductivity (10mm, W / m·K) KS L 9016:2010 0.099 0.093 0.091 0.213 0.172 Endurance KS F 4919 Not a pitcher Not a pitcher Not a pitcher Not a pitcher Not a pitcher Chloride ion penetration resistance (coulomb) KS F 2711 4 4 2 42 16 Chemical resistance (1) _Tensile strength change rate 50% lactic acid ASTM D 3912 (30 days of immersion) A A A D C 10% hydrofluoric acid B A A F C 20% sulfuric acid A A A F D Sodium hydroxide 50% A A A C B Ammonium hydroxide 30% A A A C C engine oil A A A B B ethanol A A A C B Chemical resistance (1) Growth rate change rate 50% lactic acid ASTM D 3912 (30 days of immersion) A A A D B 10% hydrofluoric acid B A A F C 20% sulfuric acid A A A F D Sodium hydroxide 50% A A A C B Ammonium hydroxide 30% A A A C B engine oil A A A C B ethanol A A A B B (1) Chemical resistance judgment criteria

[0125] As shown in Table 2 and Figures 2 to 5 above, it was confirmed that the polyurea-based surface treatment compositions for concrete structures prepared in Examples 1 to 3 of the present invention exhibited excellent film performance compared to the comparative compositions prepared in Comparative Examples 1 and 2.

[0127] As explained above, those skilled in the art to which the present invention pertains will understand that the present invention may be implemented in other specific forms without altering its technical concept or essential features. Therefore, all embodiments described above should be understood as illustrative and not restrictive. The scope of the present invention should be interpreted as including all modified or altered forms derived from the meaning and scope of the claims set forth below and their equivalents, rather than from the detailed description above.

Claims

Claim 1 A polyurea-based surface treatment composition in which a first agent and a second agent are mixed in a volume ratio of 1:0.5 to 1.5, wherein the first agent contains 100 parts by weight of isocyanate prepolymer; 1 to 10 parts by weight of tetrahexyldecyl ascorbate; and 0.1 to 5 parts by weight of phlogopite, and the second agent contains 100 parts by weight of poly(oxypropylene)diamine; 10 to 50 parts by weight of nadic methyl anhydride; 10 to 30 parts by weight of acetoacetanilide; and 10 to 30 parts by weight of diethyltoluenediamine. A polyurea-based surface treatment composition for concrete structures, comprising 1 to 10 parts by weight of one or more polyaspartate salts selected from the group consisting of sodium polyaspartate, potassium polyaspartate, and mixtures thereof, wherein the isocyanate prepolymer is prepared by reacting 100 parts by weight of norbornane diisocyanate (NBDI); 10 to 30 parts by weight of dimeryl diisocyanate (DDI); 50 to 150 parts by weight of polyoxypropylene glycol; 10 to 30 parts by weight of 3-hydroxyoxetane; and 1 to 10 parts by weight of glycidol. Claim 2 In claim 1, the phlogopite is a phlogopite coated with an adhesive polymer, and the method comprises the steps of: preparing a phlogopite dispersion by mixing 100 parts by weight of distilled water, 200 to 400 parts by weight of methanol, 1 to 10 parts by weight of an aqueous hydrochloric acid solution having a concentration of 30 to 40 weight%, 0.01 to 1 part by weight of a sulfoxymine compound, and 10 to 30 parts by weight of phlogopite; and preparing a monomer mixture by mixing N-vinylpyrrolidone, butyl acrylate, and azobisisobutyronitrile (AIBN) polymerization initiator in a weight ratio of 1:0.8 to 1.2:0.01 to 0.

3. A polyurea-based surface treatment composition for concrete structures, characterized by being prepared by a method comprising the step of: adding 1 to 20 parts by weight of the monomer mixture drop by drop to 100 parts by weight of the solid content of the phlogopite dispersion at 50 to 80 ℃, and reacting for 4 to 8 hours to produce phlogopite coated with an adhesive polymer, wherein the sulfoximine compound is one or more selected from the group consisting of thionine sulfoximine, methionine sulfoximine, 2-ethylmethionine sulfoximine, and mixtures thereof. Claim 3 A polyurea-based surface treatment composition for concrete structures according to claim 2, wherein the step of manufacturing the phlogopite coated with the adhesive polymer comprises adding 1 to 20 parts by weight of the monomer mixture drop by drop to a dispersion mixture in which 1 to 10 parts by weight of hydrogenated lecithin, 1 to 10 parts by weight of alumina fiber, and 1 to 5 parts by weight of hydroxypropyl cyclodextrin (HPCD) are mixed with 100 parts by weight of the solid content of the phlogopite dispersion at 50 to 80 ℃, and then reacting for 4 to 8 hours. Claim 4 A polyurea-based surface treatment composition for concrete structures according to claim 1, wherein the isocyanate prepolymer further contains 1 to 10 parts by weight of a cardol-based compound per 100 parts by weight of norbornane diisocyanate, and the cardol-based compound is one or more selected from the group consisting of cardoldiene (CAS No. 79473-25-9), cardoldriene (CAS No. 79473-24-8), and mixtures thereof. Claim 5 A polyurea-based surface treatment composition for concrete structures according to claim 1, wherein the first agent further contains 1 to 10 parts by weight of a pelargonate-based compound per 100 parts by weight of the isocyanate prepolymer, and the pelargonate-based compound is one or more selected from the group consisting of neopentyl glycol dipelagonate, glycerol tripelagonate, pentaerythritol tetrapelagonate, and mixtures thereof. Claim 6 A salt damage prevention method using a polyurea-based surface treatment composition for concrete structures according to any one of claims 1 to 5, comprising: a surface preparation step of removing impurities, laitance, and deteriorated areas from the surface of a concrete structure and cleaning to prepare the base surface; a primer layer formation step of applying one or more primers selected from the group consisting of silane-based primers, siloxane-based primers, silane-siloxane composite primers, silicate-based primers, epoxy-silane composite primers, and mixtures thereof; a polyurea-based intermediate layer formation step of applying the polyurea-based surface treatment composition for concrete structures; and a weather-resistant top layer formation step of applying one or more top coating agents selected from the group consisting of aliphatic polyurea-based, polyaspartic-based, aliphatic urethane-based, and mixtures thereof.

Citation Information

Patent Citations

  • Urethane-modified epoxy resin, curable composition, cured product thereof, fiber- reinforced composite material and fiber- reinforced resin molded article

    JP2015081329A

  • Water-based polyurethane resin composition

    KR1020190123260A

  • Protective coating composition for preventing deterioration and enhancing durability of concrete structures and making method using the same

    KR102601178B1